Reaproveitamento de água em uma indústria sucroalcooleira - Pereira, Milton Rogério (2010)
Sugar cane has been around since ancient times, and now the industries of sugar and alcohol are at the peak of their productivity by investing more to reduce the production cost. One of the factors that sugar and alcohol can improve is related to the losses in the processing of their products. Currently the domestic industry is subject to two major instruments of pressure. On one hand, the constraints of international trade by improving competitiveness and on the other, environmental issues and recent legal constraints of water resources management, particularly those related to charging for water use. Usina Santa Terezinha, located in Iguatemi District, city of Maringa-PR, using two sources of funding, Chapecó water from the dam to meet the cooling of bearings mills. Therefore, this paper seeks to identify the main critical points of the process responsible for the increase of water losses in the industries of sugar and alcohol and reduce the uptake current distillery. To achieve its objectives, to show the importance of reuse of wastewater generated in the industries of sugar and alcohol sector, the methodology involved two actions: a literature review and survey flowchart of water and waste in the industrial park of a unit of sugar production and alcohol in the municipality of Maringá. The study will seek to use cooling tower to reduce the temperature of the water for its and other to reuse in a closed circuit. As a result, according to the lower volume capture and return of effluents, it was possible to capture a minimum of muddy water on rainy days, having sufficient volume for recirculation in equipment and meet government requirements on the quality of effluents, in addition to paying the minimum by the capture and return of effluent when its effective recovery. The deployment of this system will cost $201.111,00 with cooling towers. Considering the cust of water collected with the effluent returned of $ 0.13 / m3, has been the end of a crop of about 160 days effective an reducion of $ 67.711,00, in compare the reduce capture.